2014
DOI: 10.3109/10717544.2014.896958
|View full text |Cite
|
Sign up to set email alerts
|

Design, development and characterization of buccal bioadhesive films of Doxepin for treatment of odontalgia

Abstract: Tricyclic antidepressants, as doxepin hydrochloride (DH), may have analgesic local effect due to its biochemical mechanism of action. Delivery of DH directly to the oral cavity could be an interesting alternative for toothache due to its analgesic local effect. One problem associated with the mucosal administration routes is the short residence time of the dosage form on the mucosal membranes. In this sense, we have developed new doxepin mucoadhesive films able of reducing pain and increasing the effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 38 publications
0
29
0
1
Order By: Relevance
“…The polymeric solution was stirred on magnetic stirrer for 2 h. The solid dispersion equivalent to 120 mg LVS was added followed by addition of plasticizer 0.7 % glycerol and 20 mg of menthol as permeation enhancer. The mixture was stirred for 30 min and then poured into Petri dish, which is stored at 4 °C to remove air bubbles entrapped and finally dried at 37 °C for 4 h. The dried films were cut into 1 cm 2 and packed in aluminum foil and stored [4,10].…”
Section: Transbuccal Film By Using Hpmc E5mentioning
confidence: 99%
See 2 more Smart Citations
“…The polymeric solution was stirred on magnetic stirrer for 2 h. The solid dispersion equivalent to 120 mg LVS was added followed by addition of plasticizer 0.7 % glycerol and 20 mg of menthol as permeation enhancer. The mixture was stirred for 30 min and then poured into Petri dish, which is stored at 4 °C to remove air bubbles entrapped and finally dried at 37 °C for 4 h. The dried films were cut into 1 cm 2 and packed in aluminum foil and stored [4,10].…”
Section: Transbuccal Film By Using Hpmc E5mentioning
confidence: 99%
“…The mixture was stirred for 30 min and then poured into petridish, which is stored at 4 °C to remove air bubbles entrapped. The patches were finally dried at 25 °C for 24 h. The dried films were cut into 1 cm 2 and packed in aluminium foil and stored [4]. F14 120 200 3 20 F15 120 300 3 20 F16 120 400 3 20 F17 120 500 3 20 F18 120 600 3 20…”
Section: Transbuccal Film By Using Chitosanmentioning
confidence: 99%
See 1 more Smart Citation
“…Mucoadhesive strength was measured using rabbit cheek pouch as biological substrate. A piece of film (size 1 cm 2 ) to be tested was cut and attached to the probe of the texture analyzer using cyanoacrylate adhesive (Castán et al, 2014). The rabbit epithelium mucosa was mounted on the stationary platform.…”
Section: Mucoadhesive Strengthmentioning
confidence: 99%
“…This alternative site offers rapid and direct delivery into the systemic circulation, easy accessibility, higher patient compliance, besides being capable of enhancing bioavailability (Palem et al, 2011). Among the various buccal dosage forms, buccal film is the most advanced and highly preferred drug delivery system on account of easy adherence to buccal mucosa, better adaptation to the mucosal surface and prolonged retention (Castán et al, 2014;Lv et al, 2014). It was also reported that the buccal delivery of selegiline is likely to enhance the absorption as well as reduce the formation of metabolites when compared to conventional therapy (Nyholm, 2006).…”
Section: Introductionmentioning
confidence: 99%